Landslides on São Miguel Island (Azores): susceptibility analysis and validation of rupture zones using a bivariate GIS-based statistical approach - Marques, R. (2019)
Since settlement of Sa˜o Miguel Island in the middle of the fifteenth century, several destructive landslides have occurred. These have been triggered by various factors, of which rainfall is the most common. Between 1900 and 2008, based on extensive documentary evidence, 193 landslide events with socio-economic impact have been identified. These events have been responsible for 67 deaths, about 20 people have been seriously injured, and dozens of houses destroyed and people rendered homeless. In this chapter, the Information Value Method is used to produce a landslide rupture susceptibility map for Sa˜o Miguel. Success and prediction rate curves (SRC and PRC) are computed and areas under the curve (AUC) calculated in order to not only support the results of modelling, but also assess the robustness of the suggested susceptibility algorithm. Twelve predisposing factors are used as independent variables and a total of 9890 landslide depletion areas are used as the dependent variable. The AUC for both the SRC and the PRC was 0.90. The methodology used for the construction of the susceptibility map was shown to be both accurate and reliable. The map is an important tool for land-use/emergency planning and for landslide risk mitigation.